2022
DOI: 10.1111/tpj.15877
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a DFR gene that controls anthocyanin accumulation in the spiny Solanum group: roles of a natural promoter variant and alternative splicing

Abstract: SUMMARY Anthocyanins are important pigments that impart color in plants. In Solanum, different species display various fruit or flower colors due to varying degrees of anthocyanin accumulation. Here we identified two anthocyanin‐free mutants from an ethylmethane sulfonate‐induced mutant library and naturally occurring mutants in Solanum melongena, with mutations in the 5′ splicing site of the second intron of dihydroflavonol‐4‐reductase (DFR) – leading to altered splicing. Further study revealed that alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…The results proved that overexpression of ZbDFR could significantly promote the accumulation of anthocyanins. Similar phenotype had been demonstrated in other plants in previous studies, such as Asparagus officinalis (Liang et al, 2022a, b) and Solanum (Wang et al, 2022a, b). After the overexpression of DFR, the calluses of A. officinalis showed a purplish red and the calluses of Solanum showed a deep purple, which were all the manifestation of a large accumulation of anthocyanins.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results proved that overexpression of ZbDFR could significantly promote the accumulation of anthocyanins. Similar phenotype had been demonstrated in other plants in previous studies, such as Asparagus officinalis (Liang et al, 2022a, b) and Solanum (Wang et al, 2022a, b). After the overexpression of DFR, the calluses of A. officinalis showed a purplish red and the calluses of Solanum showed a deep purple, which were all the manifestation of a large accumulation of anthocyanins.…”
Section: Discussionsupporting
confidence: 88%
“…A study of Rubus occidentalis also proved that cyanidin‐3‐O‐rutinoside and cyanidin‐3‐O‐glucoside were important to fruit color (Dayeon & Eunmi, 2018). In Triticum aestivum , the accumulation of cyanidin‐3‐O‐rutinoside, cyanidin‐3‐O‐glucoside and other anthocyanins gave the seeds a deeper purplish red color and a higher nutritional value (Wang et al, 2022a, b). All these results made the conclusion that cyanidin‐3‐O‐rutinoside and cyanidin‐3‐O‐glucoside were the key pigment compound for Z. bungeanum peels more convincing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the expression of anthocyanin and proanthocyanidin biosynthesis genes DFR, ANS, UGT, LAR, ANR showed a downward trend during petal development (Fig 9). FLS and DFR are key structural genes by which flavonoids enter different synthetic branches (Kubra et al ., 2021; Liu et al ., 2021; Wang et al ., 2022), and overexpression of FLS increases the biosynthesis of flavonols (Park et al ., 2020; Yu et al ., 2021). Heterologous expression of Rosa rugosa RrDFR1 and Petunia hybrida PhDFR in tobacco has been reported to inhibit the expression of the endogenous NtFLS and promote the accumulation of anthocyanins (Luo et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoid biosynthetic genes are regulated by special ternary transcriptional factor complexes of MYB-Basic, helix-loop-helix, and WD40 (MBW) ( Xu et al., 2015 ). It has been revealed that mutation in the promotor region of dihydroflavonol-4-reductase (DFR) and alternative splicing of DFR leads to alteration in the accumulation of anthocyanin pigment in the solanum group ( Wang et al., 2022 ). In the chrysanthemum transcriptional factor, cmbHLH2 generates two transcripts: fully transcribed cmbHLH2 full and truncated short-length cmbHLH2 short .…”
Section: Applications Of As In Transcriptional Repressionmentioning
confidence: 99%